PENGENALAN DAN PENGGUNAAN DASAR ALAT-ALAT TANGAN OTOMOTIF SISWA KELAS X TKR DI SMK YPT PURWOREJO - Fendi Setiawan; Aci Primartadi; Widiyatmoko (STKIP Subang, 2026)
This study aims to determine the level of understanding and knowledge of Class X TKR students at SMK YPT Purworejo regarding the types, functions, and basic use of automotive hand tools. The research employs a quantitative descriptive method using a cross-sectional survey design. The subjects were all 30 Class X TKR students in the 2025/2026 academic year (total sampling). Data were collected through a 30-item multiple-choice cognitive test validated with Pearson Product Moment correlation and reliability-tested with Cronbach’s Alpha, complemented by structured observation (15 aspects, scale 1–4) and guided interviews. Data were analyzed using descriptive statistics and percentage-frequency distribution with five classification categories: Very Good (81–100%), Good (66–80%), Fair (56–65%), Poor (41–55%), and Not Good (25–40%). Results showed a mean cognitive test score of 69.4 (Good category), with distribution: 3 students (10.0%) Very Good, 9 students (30.0%) Good, 10 students (33.3%) Fair, 7 students (23.3%) Poor, and 1 student (3.3%) Not Good. The observation mean was 78.5% (Good category), with the highest scores on basic tool recognition and work attitude (85.0–90.0%), and the lowest on precision measuring instruments (62.5%). Key constraints identified include: limited availability of practical tools, monotonous teaching methods, and diverse student backgrounds. These findings provide an empirical baseline for improving hand tool competency learning in vocational automotive education.